The effect of Evening Primrose on hot flashes in menopausal women - Bahareh Motaghi Dastenaei; Faranak Safdari; Lobat Jafarzadeh; Ziba Raisi Dehkordi; Mohsen Taghizadeh; Maryam Nikzad (Mashhad University of Medical Sciences, 2017)
Introduction: Menopause for women is a global phenomenon. Flushing is of the symptoms which women experience during menopause. The treatment which is now used for flushing is hormone replacement that has many side-effects. One of the alternatives for hormone therapy is the use of plants from the family of phytoestrogens, such as evening primrose. This study was performed with aim to evaluate the effect of evening primrose on hot flashes during menopause. Methods: This triple-blind clinical trial study was performed on 100 postmenopausal women referred to the health centers of Dastena in 2015. The subjects were assigned to two groups of placebo (n=50) evening primrose (n=50). The women participating in this study used Perle's a warm evening primrose plant or placebo twice a day for one month. Kuperman questionnaire was used to assess symptoms of menopause. Data was analyzed by SPSS software (version 11) and Chi-square and t-test. P<0.05 was considered significant. Results: The use of evening primrose had significant effect to reduce the severity, duration and frequency of hot flashes in the evening primrose group compared to placebo (P <0.001). Conclusion: The use of evening primrose was effective in reducing hot flashes in women, and can be used as a supplement or hormone replacement therapy to improve the symptoms of menopause in women.